Self-assembly of shape-controlled nanoparticles into tunable two- dimensional metasurfaces at the oil- water interface - Yang, Yijie (2018)
This thesis includes my four-year researches on the fabrication of tunable twodimensional (2D) metasurfaces by assembling shape-controlled nanoparticles at the oilwater interface. Our aim is to break the limited planar structure and achieve the high tunability of macroscopic superstructures. In Chapter 1, we summarize recent studies on the fabrication of 2D structures, self-assembly method, parameters influencing assembled structure and the application of plasmonic structure. In Chapter 2, we report a new chemical strategy of controlling surface distribution to achieve tunable metasurfaces with non-planar nanocube orientations, creating novel lattice-dependent field localization patterns. In Chapter 3, we further utilize solvent-tunable molecular-level polymer conformation changes to achieve ‘multiple metacrystals using one nanoparticle with one chemical functionality’. This method breaks the limitation of changing surface chemistry by replacing surface ligands. In Chapter 4, we study the shape-mediated structure transformation and establish a phase diagram of polyhedral particles to indicate the relationship between vertex truncation, surface functionalization, interfacial position and superstructure. In the above works, we study the interfacial behavior by understanding the interaction between particle surface and two liquid phase. In Chapter 5, we study the particle-particle interaction to achieve the control over assembled structure by using two surface ligands with similar bulk wettability.